A Practical and Efficient Synthesis of (±)-Anatabine - Rossi, Federico V.; Ballini, Roberto; Barboni, Luciano; Allegrini, Pietro; Palmieri, Alessandro (Synthesis, 2018)
A new efficient synthesis of racemic anatabine is reported. The title target was obtained in an excellent overall yield of 70%, by a five-step synthesis, using cheap reagents and mild reaction conditions.
Keywords: anatabine; heterocycles; total synthesis; tobacco alkaloids; ring closure